Atheists in America - Brewster, Melanie E. (New York : Columbia University Press, 2014)
This collection features more than two dozen narratives by atheists hailing from different backgrounds across the United States. Ranging in age, race, sexual orientation, and firmness in their irreligiosity, these individuals address religious deconversion, community building, parenting, and romantic relationships, providing a nuanced look at living without God in a predominantly Christian nation. These narratives illuminate the complexities and consequences for nonbelievers in the United States. Stepping away from religious belief can have serious social and existential ramifications, forcin
Includes bibliographical references.
Description based on print version record.
Keywords: Atheists -- United States -- Biography; Atheism -- United States; BIOGRAPHY & AUTOBIOGRAPHY / Literary; LITERARY CRITICISM / Poetry; Electronic books